Investigation on the application of physical mental health education in the exploration of ideological and political education of Party building - Jing Dai; Haifang Zhang, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This study investigates the application of physical mental health education (MHE) to the investigation of ideological and political education (IPE) in the context of Party formation. This article utilized the methods of literature, teaching observation, experiment, and mathematical statistics. The research object was the ideological and political teaching design of college sports and health basketball courses, and the practice object was first-year students. Regarding the ideological and political integration of political identity education, there was a significant difference between the practice class and the control class, and the mean of each question in the practice class was higher than in the control class. It is essential to comprehend the mental health of college students in-depth and to integrate it through IPE, to establish a curriculum ideological and political construction system, and to guarantee the sustainable development of curriculum IPE from the mechanism.